Pengembangan Keterampilan Academic English Writing Mahasiswa Semester IV Jurusan Pariwisata Politeknik Negeri Manado Melalui Metode Penerjamahan - Agustinus Lumettu (PolimdoSains, 2020)
English competence is determined by its grammar mastery, more specifically Academic English Competence. In daily conversation, mastery of grammar is not the key point but in Academic English, the mastery of grammatical sentences is an important aspect. The general objective of this research is to prepare the higher semester students to master Academic English in order that they pass the test for further studies both in domestic and foreign universities as well as pass the test for employment recruitment both in public and private sectors that require good Academic English mastery. The specific objective of this research is to enable the target students to fulfill the requirements for undertaking internship in foreign countries and write internship report in English as well as write the Final Project / Skripsi in English. The method used in developing the students’ Academic Writing Skill is Translation Method since this method provides ample grammatical exercises starting from sentence level translation , paragraph level translation and essay level translation as well as vocabulary practice .Further, the students are given examples of ideas in writing sentences, paragraphs and essays. Finally the students are trained to write tourism topics directly in English without depending on translation. The method of this research is Qualitative method. The results of research show that translation Method is very effective in developing the students’ Academic Writing Skills. The final test average score obtained by the Experimental group is 23 % higher than that of the Control group.